Isolation and Identification of Clostridium difficile from Antibiotic- Associated Diarrhea and Colitis in Iraqi children, using API20A Anaerobic system. (Journal of the College of Basic Education, 2022)
Clostridium difficile were isolated by 51 (21.25%) from a total of 240 stool sample collected from children having diarrhea and colitis at ages from after birth to 15 years old from Baghdad hospitals, who were under treatment with broad spectrum antibiotics, and Sample were taken during the period of first of June 2013 till the end of april 2014. Also 80 stool samples were collected from healthy ,non diarrhea children as controls. Morphological and API 20A tests were used for the identification of this bacterium to evaluate the performance of the API 20A anaerobe system in definitively identifying strains of C. difficile. . This study shows that females were more infected than males .Overall positivity was (21.25%)in this study group compared to controls (P<0.05). The isolation percent from age <5years was (18.75%) , while it in age>5years was( 2. 5 %) . It was found that this percent decreased with age get older.